The Effect of Differentiated Learning Approach on Cognitive Development in Early Childhood at TK Negeri 2 Kamang Baru, Kamang Baru District, Sijunjung Regency - Swari, Suci Indra; Isnaini, Isnaini; Andre, Lesis; Arsis, Asi Noflanda (The Future of Education Journal, 2025)
Early childhood education is a fundamental stage in building a child's cognitive foundation. However, the reality at Kamang Baru 2 Kindergarten shows that monotonous conventional learning methods are still used, hindering children's exploration and development of thinking. By accommodating these differences, differentiated learning enables students to learn in a more optimal, relevant, and meaningful way. Differentiated learning enables students to develop their talents through potential identification, where teachers can observe and recognize individual talents in both academic (such as math, science) and non-academic (art, sports) areas. This study aims to determine the effect of a differentiated learning approach on the cognitive development of children aged 5–6 years.This quantitative study, using a one-group pretest-posttest pre-experimental design, was conducted in November 2024 at Kamang Baru 2 Kindergarten to measure the effect of differentiated learning on the cognitive development of children aged 5–6 years. The population consisted of all 64 students at Kamang Baru 2 Kindergarten. The sample consisted of 16 children in grade B2 selected using a cluster sampling technique. The instrument consisted of an observation sheet using a Likert scale of 1–4, validated through content validity. Data were collected through observation and documentation, then analyzed using descriptive and inferential statistics, including t-tests and N-Gain tests, to determine the effectiveness of the treatment.Based on the research results, it can be seen that the t0 value is greater than the t-table, namely 31.36>2.602. Therefore, the alternative hypothesis is accepted: differentiated learning influences the cognitive development of early childhood. Thus, there is a significant difference between the pre-test and post-test in the sample group. Therefore, hypothesis Hₐ is accepted and hypothesis Hₒ is rejected. Therefore, it can be concluded that differentiated learning can be applied to improve the cognitive development of early childhood. It can be concluded that the results of statistical testing of the alternative hypothesis (Hₐ) indicate that differentiated learning influences cognitive development in children.